Colpocleisis: A Survey of Current Practice Patterns. Issue 4 (July 2017) - Jones, Keisha; Wang, Gary; Romano, Robert; St Marie, Peter; Harmanli, Oz
Abstract : Background: Currently, there are no standard treatment guidelines for colpocleisis. Clinical practice varies widely for this safe and effective procedure. Objective: The aim of this study was to evaluate the current practice patterns in the United States among surgeons who perform colpocleisis. Methods: A 27-item anonymous Web-based survey was sent to all practicing physicians affiliated with the American Urogynecologic Society. It consisted of questions regarding the demographic background of the physicians and their current practice as it relates to colpocleisis. Results: Of the 1422 physicians contacted, 322 responded (23%) to the questionnaire. Slightly more than half were female with an average time of 15 years in practice. The majority of respondents (79%) were urogynecologists. Most surgeons chose colpocleisis for its high success rate, short operating time, and low risk of complications. Approximately half of the providers performed both LeFort and total colpocleisis. Only 18% performed a routine hysterectomy at the time of surgery. Routine preoperative endometrial evaluation was preferred by 68% of the respondents, with 81% utilizing a transvaginal ultrasound first. Almost all providers would perform concomitant incontinence procedures, with 54% requiring a positive cough stress test and normal postvoid residual. Conclusions: There is variation in the current practice of colpocleisis in the United States. LeFort colpocleisis is most commonly performed, and routine hysterectomy is uncommon. Two thirds of surgeons evaluate the endometrium prior to surgery. Concomitant anti-incontinence procedures appear to be standard. Abstract : LeFort colpocleisis is the most common vaginal obliterative surgery in the United States. Concomitant hysterectomy is rare, while incontinence procedures appear to be standard.